2016
DOI: 10.1287/mnsc.2015.2224
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Age and Expertise on Product Evaluations: Does the Type of Information Matter?

Abstract: T o better understand two large consumer segments, the boomers and the echo-boomers, we examine whether and why experts and novices from these two segments rely on attribute versus benefit information in product evaluations. In four studies, we show that expertise affects younger consumers, such that younger novices evaluate products more favorably when the descriptions feature benefit information, whereas younger experts evaluate products more favorably when the descriptions feature attribute information. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…We raise also the observation that managers' individual features (traits) can influence construal in certain circumstances, such as a managers' personal characteristics (age, or nationality) (Wiesenfeld et al, 2017). Limited research has explored the impact of managers' traits on construal and the effects of traits such as age or experience has been explored mainly in terms of consumer decision‐making (e.g., see Wang and Cole, 2016). While recent studies have sought to address the role of managerial expertise in construal level (e.g., see Mount et al, 2021), these found little influence from manager age, or their organizational tenure.…”
Section: Discussion Implications and Conclusionmentioning
confidence: 99%
“…We raise also the observation that managers' individual features (traits) can influence construal in certain circumstances, such as a managers' personal characteristics (age, or nationality) (Wiesenfeld et al, 2017). Limited research has explored the impact of managers' traits on construal and the effects of traits such as age or experience has been explored mainly in terms of consumer decision‐making (e.g., see Wang and Cole, 2016). While recent studies have sought to address the role of managerial expertise in construal level (e.g., see Mount et al, 2021), these found little influence from manager age, or their organizational tenure.…”
Section: Discussion Implications and Conclusionmentioning
confidence: 99%
“… 35 In addition to the effects of cost-related messaging, trust may also be influenced by the level of detail and the amount of information presented to older populations. 32 , 33 , 34 , 35 , 36 Older individuals prefer benefit information (information about the general improvements they may experience as a result of a decision) compared to attribute information (specific information to inform a decision such as plan attributes and benefit design). 34 , 35 Based on the pharmacy service description, it appears that the information provided by staff emphasized specific plan attributes and cost-related information like premiums, copayments, deductibles, and medication costs.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewer expertise is the perceived diagnosticity of attributes and benefits and the process of conducting product information. Based on the theories from information systems and personality psychology, Wang & Cole investigated how the reviewer's expertise affects reviewer satisfaction and found that a leisure trip positively moderates the impact of reviewer expertise on satisfaction [15]. There are similarities between product satisfaction and consumer satisfaction.…”
Section: Consumer Factorsmentioning
confidence: 99%